(untitled) (Economics and region, 2024)
The article has aimed to consider predominant research streams in the domain of omnichannel from the point of view of marketing management. Based on the growth rate of papers dedicated to omnichannel research in the SCOPUS database, three periods within 2013–2023 of publication activity have been distinguished. The main research streams as well as their peculiarities within periods have been defined. The deployment of research streams has been presented. At the beginning of the research period, the main focus was on retailing and its benefits. Then the main interest was shifted to the theme of consumer behavior and engagement and close related themes such as channel integration as well as impact on retail operation and some off-topics. Overall, the results of the study have given a theoretical and methodological basis for further research in the domain of omnichannel.